BEHAVIOR OF THE ARTERIAL PRESSURE, CARDIAC FREQUENCY AND OF THE HAIR GLICEMIA WITH ADULTS PRACTICING OF YOUNG SPINNING ® WHEN SUBMITTED TO THE ASTRAND PROTOCOL (Fiep Bulletin - online, 2014)
Nowadays the health professions worrying to organizing your evaluations and conducts in protocols, these are studied, validated and placed as consent. It is like this of great importance the study of those protocols and the alterations generated in the individual. This research has as objective evaluates blood pressure systolic (SAP) and diastolic (DAP) alterations, Heart Frequency (H.R) and Capillary Glycemy in individuals submitted to the Astrand protocol, a test of cardiopulmonary evaluation which a load submaximum is used. 20 adults people were selected, both sexes, healthy with little or any physical activity. After explanations the individuals answered to the questionnaire of Habitual Physical Activities and the PAR Q YOU, and they signed the Term of Consent. Soon after they were separate in two groups. A group control with 10 individuals and a group test with 10 that ingested sucrose (50 ml orange juice) one hour before the beginning of the protocol. In both groups it was evaluated arterial pressure, C.F in the rest, 5th and 6th minute. The measure of the capillary glycemy in the group test was accomplished before the ingestion of the sucrose and after the Astrand protocol. Statistical analysis was accomplished being used the student Test t.  the results showed means elevation statistically of FC and rest PASin relation to C.F and PAS of the 5th and 6th minute of the test, but there was not means elevation statistically of PAD of the rest in relation of 5th and 6th minute neither of the glycemy per and post protocol of the test group in relation to the control group.
Keywords: Blood Pressure; Heart Frequency; Capillary Glycemy.